A multi-criteria optimization for a radial heat sink with semicircular fins based on the design of experiments approach - Yousif Hashim Hussein; Tahseen Ahmad Tahseen; Abdulrazzak Akroot; M.A.H. Mithu; Ammar M. Abdulateef (Case Studies in Thermal Engineering)
Radial fins play a crucial role in enhancing energy efficiency and supporting sustainable industrial practices by optimizing heat transfer, aligning with the Sustainable Development Goals (SDGs). Addressing the need for high-efficiency systems to reduce greenhouse gas emissions, this study highlights the importance of optimizing factors in a General Factorial Design (GFD). Factors were coded and scaled within the range of +1 to −1, accounting for variations in the units of independent variables. This study utilized the Nusselt number and thermal resistance, along with an effective regression analysis, to develop a novel predictive model. Key performance indicators included R2, adjusted R2, predicted R2, coefficient of variation (CV), and parameter separation from the best-fit results. The proposed model demonstrated remarkable accuracy in predicting the Nusselt number, with values of R2, predicted R2, adjusted R2, and CV at 98.15 %, 97.08 %, 94.87 %, and 2.44 %, respectively. For thermal resistance, the corresponding values were 97.91 % for predicted R2, 96.70 % for adjusted R2, 94.21 % for CV, and 3.33 % for parameter separation. Therefore, it is evident that the proposed model is highly accurate in predicting semicircular radial heat sink performance, offering a robust tool for future heat sink designs and sustainable thermal management systems.